2015
DOI: 10.1016/j.jacc.2015.07.066
|View full text |Cite|
|
Sign up to set email alerts
|

Implications of Coronary Artery Calcium Testing Among Statin Candidates According to American College of Cardiology/American Heart Association Cholesterol Management Guidelines

Abstract: Significant ASCVD risk heterogeneity exists among those eligible for statins according to the new guidelines. The absence of CAC reclassifies approximately one-half of candidates as not eligible for statin therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
251
0
11

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 424 publications
(274 citation statements)
references
References 29 publications
12
251
0
11
Order By: Relevance
“…Currently, CAC assessment is given a IIb recommendation to be considered in asymptomatic individuals in whom the decision to start statin therapy remains uncertain after risk discussion [3]. Our findings support the use of CAC scanning to identify those at higher risk, but also highlight an important and often overlooked aspect of CAC scanning: the prognostic power of a zero CAC score [19,20].…”
Section: Cac In Low Risk Groupssupporting
confidence: 63%
“…Currently, CAC assessment is given a IIb recommendation to be considered in asymptomatic individuals in whom the decision to start statin therapy remains uncertain after risk discussion [3]. Our findings support the use of CAC scanning to identify those at higher risk, but also highlight an important and often overlooked aspect of CAC scanning: the prognostic power of a zero CAC score [19,20].…”
Section: Cac In Low Risk Groupssupporting
confidence: 63%
“…New risk equations based on more modern data may allow for more accurate risk assessment. Further risk assessment with CAC testing may provide a more robust method of individualized risk assessment,24 and CAC scoring has been hypothesized to more accurately identify individuals who are likely to benefit from statin therapy 15. In our study, we found that 37% and 41% of individuals who are statin eligible by USPSTF and ACC/AHA, respectively, had zero CAC, a finding associated with low ASCVD rates even in the presence of traditional ASCVD risk factors 25…”
Section: Discussionmentioning
confidence: 60%
“…More than 50% of the discordant group had a CAC score of zero and event rates varied significantly according to baseline CAC. Prior research has hypothesized that CAC could be utilized to more effectively allocate statin therapy to individuals most likely to benefit 15. The arbitrary nature of risk thresholds and the lack of definitive trial data for the utility of CAC as well as in individuals at elevated ASCVD risk because of age alone highlight the importance of the clinician–patient risk discussion in making the decision to start statin therapy 3…”
Section: Discussionmentioning
confidence: 99%
“…15 Of 2966 participants eligible for statins (i.e. statin either recommended or considered), 1316 (44%) had a CACS = 0 at baseline and an observed 10-year ASCVD event rate of 4.2 per 1000 person-years.…”
Section: Computed Tomographymentioning
confidence: 99%
“…istraživali su vrijednost CACS = 0 u reklasifikaciji bolesnika koji trenutačno ispunjavaju uvjete za statine u kategoriji niskoga rizika, pri čemu terapija statinima možda više nije potrebna. 15 Od 2966 sudionika koji su ispunjavali kriterije za terapiju statinima (statini preporučeni ili razmatrani), 1316 (44 %) imalo je CACS = 0 u vrijeme uključivanja i promatranu 10-godišnju ASCVD stopu događaja 4,2 na 1000 osoba/godina. Stoga bi šira upotreba CACS-a mogla pomoći u snizivanju kategorije rizika znatnoga study including 150 non-ischaemic cardiomyopathy patients, 50% of them with significant secondary mitral regurgitation.…”
unclassified